NEED TO BE BOLD IN TRANSFORMING HIGHER EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
NILAI, NEGERI SEMBILAN, 13 December 2016 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Datuk Dr. Asma Ismail said that in order to transform higher education, we have to be bold in making changes, with ‘bold’ being the key term for change.